ترجمة لسجل رسمي حول أربعــــة وسبـعــون أسير بروفنســـال أُعيد شراءهم أو تم تبادلهم من قبل السييور دو تروبير: A Report Of Seventy-four Prisoners Of France Bought Out Or Exchanged By The Sieur De Trubert - بوزيد, صليحة (Maalim, 2021)
In this article, we have translated one of the most important documents on the question of the slavery (ransom of prisoners) between Algeria and France in the 17th century. The report is entitled 'A report of seventy-four prisoners of France bought out or exchanged by the Sieur de Trubert, published with a historical comment by Mr Arnaud de Angel, a correspondent of the Ministry of Public Instructions, quoted in the Paris Historical and Philosophical Bulletin, National Press in 1906. Registration at the Overseas Archives Center in Aix-en-Provence, France, bears the following numbering: B.2787.